The crystal structure of (3′-(2-bromophenyl)-2-phenyl-[2,2′-bioxiran]-3-yl)(phenyl)methanone, C92H68O12Br4 - Li Chengjuan; Li Yingjie; Wang Aoqi; Xi Shiqi; Zhang Yalin (Zeitschrift für Kristallographie - New Crystal Structures)
C92H68O12Br4, monoclinic, P21/c (no. 14), a = 12.3604(11) Å, b = 9.8658(9) Å, c = 15.2010(13) Å, β = 93.773(2)∘, V = 1849.7(3) Å3, Z = 4, R gt(F) = 0.0697, wR ref(F 2) = 0.1790, T = 298.15 K.